Evaluation of early embrionic development after natural mating using ultrasonography in bos indicus cows in the humid tropics of Costa Rica - Chávez, D. (2008)
Fifty-eight nursing Zebu cows averaging 5922 days postpartum were used to evaluate the early embryonic development by ultrasound under a natural mating system (bulls A to F). Three consecutive mating periods of 21 days were established. Sixty two percent of the animals were diagnosed as pregnant (36/58). During the first period (AB) 76% (27/36) of the animals become pregnant, 17% (6/36) during the second (CD) and 9% (3/36) in the last mating period (EF). Sixty two percent of the animals were true positives (animals found pregnant diagnosed by ultrasound (US), and conforming with the embryonic scale proposed by Rosiles et al. (2006); 12% (n=7) of false negatives (pregnant cows by US but not conforming with the scale); 2% (n=1) of false positives (pregnant cows, evaluated with US and conforming with the embryonic scale but not pregnant at the end of the study); and a 26% (n=15) of true negatives (not pregnancy evaluated with US). The sensitivity of the test was 97%, with a specificity of 68% with a positive predictive value of 83% and a negative predictive value of 6%. Relation between the measuring scale of embryo development and the results obtained by ultrasonography was k=0.69. No significant correlation were observed between body condition score (BCS) evaluation and body fat (BF) measurement at any of the three evaluations performed after mating, however, measurements of BCS and BF among time showed a positive correlation (0.48 P <0.05, 0.29, P<0.07, respectively) from the beginning of the evaluation period to the end of the trial. Ultrasonography to monitor embryonic development to determine the early establishment of pregnancy in natural mating reproductive programs can be a valuable technique to monitor reproductive efficiency.